THE EFFECT OF LEARNING STRATEGIES AND COGNITIVE STYLE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Siregar, Indra Kurniawan; Lubis, Rica Umrina; Ali, Muttaqin Kholis (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The objectives of the study were to (1) determine students' achievement in reading comprehension as taught by reciprocal teaching (RT) and collaborative strategies reading (CSR); (2) determine students' achievement in having dependent and independent cognitive styles; and (3) determine how learning strategies and cognitive style affect one another. The research population comprised 154 students from five classrooms in SMP Negeri 1 Angkola Timur's VIII class. Sixty-one students were sampled using cluster random sampling; of these, thirty students from class VIII-2 were taught the reciprocal teaching-learning strategy, and thirty students from class VIII-1 were taught the collaborative strategic reading (CSR) learning technique. The test was used as a means of gathering data. The findings indicated that: (1) students taught the Collaborative Strategic Reading (CSR) learning strategy X ̅ = 16.53 had higher achievement than students taught the Reciprocal Teaching learning strategy X ̅ = 15.43; (2) students with field-independent cognitive style X ̅ = 16.09 had achievement than students with field-dependent cognitive style X ̅ ̅ = 15.80 with Fcount = 7.79 > Ftable = 1.00; and (3) there is an interaction between learning strategies and cognitive styles on reading comprehension achievement.